The Russia Conference Papers 2021 - Šrāders, Sandis; Veebel, Viljar (University of Tartu Press, 2021)
This publication discusses Russia's foreign, security, defence, and military policies from both Euro-Atlantic and Russian perspectives. More importantly - this work acts as an essential platform for analysing the security challenges linked with Russia and the required responses of the Euro-Atlantic community to the complex challenges posed by Russia's actions in the region and on a global scale. This collection of articles has emphasised the perception of Russia shared by NATO, the European Union, Russian pundits, and the regional actors. The uniqueness of the current volume proposes an equal measure of pragmatic policy solutions and academic ones to these critical global issues. From the Euro-Atlantic side, the work pays special attention to the efficiency of the transatlantic deterrence of Russia and its importance for security in the wider-Baltic region. The articles also focus on the multiple Russian hybrid actions of 2019-2021, the lessons learned from Russia's actions in Ukraine, Belarus, Armenia, and potential threats that might emanate from Russia's military modernisation. Thinking from the Russian side, elite and domestic discourses, popular perceptions, and future potentialities are presented and synthesised into this broader paradigm.